Analisis Sektor Unggulan dan Pergeseran Struktur Ekonomi dengan Pendekatan Location Quotient dan Shift Share - Khafifah Indahsari Arif Sulnas; Basri Bado; Muhammad Syafri; Abdul Rajab; Citra Ayni Kamaruddin (Forum Kerjasama Pendidikan Tinggi, 2026)
The economic structure of Pinrang Regency shows the diversity of business sectors with the contribution of GDP which is still dominated by the primary sector. Based on BPS data for 2015-2024, it shows that the growth rate in the agriculture, forestry, and fisheries sectors is only 4.23 percent and this value is smaller than the average GDP growth of Pinrang Regency, which is 5.71 percent. On the other hand, the information and communication sector recorded the highest growth, namely 9.08 percent. The increase in the growth rate in the secondary and tertiary sectors with a high percentage shows that there are changes in several economic sectors that support economic growth in Pinrang Regency. This research aims to find out the leading sectors and shifts in economic structure as the basis for development planning in Pinrang Regency. The research was carried out quantitatively by utilizing secondary data from BPS, especially GDP data for Pinrang Regency and South Sulawesi Province in 2015–2024. The analysis was carried out using location quotient analysis techniques and shift share analysis. The results of the location quotient analysis show that Pinrang Regency has three leading sectors, namely (1) agriculture, forestry, and fisheries with an average LQ of 2.19; (2) electricity and gas procurement with an average LQ of 1.22; and (3) wholesale and retail trade, car and motorcycle repair with an average LQ of 1.02. Furthermore, the findings of the shift share analysis reveal that Pinrang Regency has experienced a shift in economic structure during the 2015–2024 period, shifting from the primary sector to the tertiary sector. This structural change is reflected in the increase in the contribution of the tertiary sector, especially the increase in dominance in the large trade and retail sectors, car and motorcycle repair with a net shift of 38.85 billion rupiah.